A experiência discursiva e a singularidade: levantamento de questões no campo da aquisição de linguagem - Carvalho, Glória; Rozental, Eva (Cadernos de Linguagem e Sociedade, 2010)
The present paper is an attempt to discuss the relationship between shared discursive experience and the child’s singular speech, at an early stage of his/her linguistic course. The infant’s unusual utterances were selected and taken as units of analysis, that is, the types of utterances which are unfamiliar to the adult, thus highlighting the singularity aspect. By confronting verbal data of a diad (mother-child), the relevance of considering the discursive experience background between the two speakers stood out within the study of the changes occurring in the subject, from his/her condition of non-speaker into a new condition of speaker. Nevertheless, there is an indication that there would be a language movement towards two poles: metaphorical and metonymical. These would act on such discursive experience, making it return, in the child’s utterances as a different, singular structure.